Contribution of alveolar type II cell‐derived cyclooxygenase‐2 to basal airway function, lung inflammation, and lung fibrosis. Issue 1 (22nd September 2015) - Cheng, Jennifer; Dackor, Ryan T.; Bradbury, J. Alyce; Li, g; DeGraff, Laura M.; Hong, Lee K.; King, Debra; Lih, Fred B.; Gruzdev, Artiom; Edin, Matthew L.; Travlos, Gregory S.; Flake, Gordon P.; et al.
ABSTRACT: Cyclooxygenase (COX)‐2 has been shown to be involved in regulating basal airway function, bacterial LPS‐induced airway hyperresponsiveness (AHR) and lung inflammation, and bleomycin‐induced lung fibrosis; however, the cellular source of COX‐2 that underlies these effects is unknown. We generated mice with alveolar type II (ATII) cell‐specific knockdown of COX‐2 (AT2CC‐/‐), to examine the role of ATII cell‐derived prostaglandins (PGs) in these processes. Specific knockdown of COX‐2 was confirmed by real‐time RT‐PCR and Western blot analyses. LC/MS/MS analysis showed that ATII cells produced PGs. Basal airway responsiveness of AT2CC ‐/‐ mice was decreased compared to that of wild‐type (WT) mice. LPS‐induced hypothermic response, infiltration of inflammatory cells into the airway, and lung inflammation were enhanced in AT2CC ‐/‐ mice relative to WT controls; however, LPS‐induced AHR and proinflammatory cytokine and chemokine expression were similar between the genotypes. After 21 d of bleomycin administration, AT2CC‐/‐mice behaved in a manner similar to WT mice. Thus, ATII cell‐derived COX‐2 plays an important role in regulating basal airway function and LPS‐induced lung inflammation, but does not play a role in bleomycin‐induced fibrosis. These findings provide insight into the cellular source of COX‐2 related to these lung phenotypes.—Cheng, J., Dackor, R. T., Bradbury, J. A., Li, H., DeGraff, L. M., Hong, L. K., King, D., Lih, F. B., Gruzdev, A., Edin, M. L., Travlos, G. S., Flake, G. P., Tomer, K. B., Zeldin, D. C. Contribution of alveolar type II cell‐derived cyclooxygenase‐2 to basal airway function, lung inflammation, and lung fibrosis. FASEB J. 30, 160‐173 (2016). www.fasebj.org